Design and hydrodynamic analysis of subsea development automatic placement devices - Han, Jun; He, Zai-Ming; Ma, Ling; Li, Xiu-Feng; Wan, Jiang-Long (Frontiers in Mechanical Engineering, 2025)
In response to the problems of low efficiency and safety hazards in traditional subsea pipeline intersection isolation release operations, this study designs a new type of automatic deployment device for subsea oil and gas pipeline intersection isolation, aimed at replacing manual and unmanned underwater vehicles (ROVs) for underwater deployment and monitoring. The device adopts an innovative framework structure design, significantly improving its resistance to water flow, and enhancing the operability and accuracy of underwater operations through a ducted propeller propulsion system. This study used computational fluid dynamics (CFD) combined with multiple reference frame (MRF) method to conduct detailed simulation analysis of the fluid dynamics characteristics of the device under different motion states, and explored its optimal working conditions. The simulation results show that during rotational motion, when the flow velocity exceeds 0.5 m/s, the resistance experienced by the device significantly increases, reaching a maximum of 7066.33 N. In addition, this study conducted an in-depth analysis of the causes of flow separation and resistance distribution under different motion states, revealing the important impact of frame style exterior design on the hydrodynamic performance and stability of the device. The research results indicate that the automatic placement device can efficiently complete the placement task of isolation materials in a water flow environment of 0.75 m/s, with a maximum driving torque of 6750 N*m, and has good engineering application prospects. The design proposed in this article not only provides a new perspective and solution for deep-sea pipeline protection technology, but also lays an important theoretical foundation for research and application in this field through innovative structural design and advanced simulation analysis methods.